Bahaya Kosmetika Pemutih yang Mengandung Merkuri dan Hidroquinon serta Pelatihan Pengecekan Registrasi Kosmetika di Rumah Sakit Gunung Jati Cirebon - Sulistiorini Indriaty; Nur Rahmi Hidayati; Arsyad Bachtiar (Jurnal Surya Masyarakat, 2018)
Skin whitening products are one of the cosmetic products that contain active ingredients that can suppress or inhibit the formation of melanin or eliminate melanin that has been formed so as to give a whiter skin tone. Limitations of knowledge about various whitening cosmetic products make people do not know the negative effects that arise if not careful. Mercury and hydroquinone are some active substances that are often misused by illegal cosmetics manufacturers. But in fact the abuse of mercury and hydroquinone is still common in whitening products. This activity was carried out with the aim of providing knowledge and skills to the community, especially waiting room patients in the outpatient clinic at Gunung Jati Cirebon Hospital in terms of checking the registration number for cosmetics. This activity was carried out with counseling methods and question and answer about the material hazards of using whitening cosmetics containing mercury and Hydroquinone is followed by training in checking the registration number for cosmetics using an Android cellphone. From this activity it can be concluded that patients are more aware of the dangers of mercury and hydroquinone and can directly check cosmetic products that are commonly used everyday.